Is stock market overpriced? A benchmark approach - Riza Emekter; Robert Beaves; Zane Dennick-Ream (Cogent Economics & Finance, 2018)
The fact that stock market is unpredictable does not deter investors, pundits, and academicians from speculating about the next market move. This paper uses multiple benchmarks to judge the current level of the stock market. Among those benchmarks are bonds; commodities; REITs; international stocks; company earnings, sales, and profits; and GDP. Ten-year moving averages of benchmark variables are individually and then collectively compared with S&P 500 index. Although our analysis finds that fundamentals do not support the current high level of the stock market, we do find evidence that a rational bubble exists in that market using the duration dependence test.
Keywords: 330; Standard and Poor ’ s 500 index (SPX); duration dependence test; CAPE